Informal Social Control of Crime in High Drug Use Neighborhoods in Louisville and Lexington, Kentucky, 2000 - Warner, Barbara D. ([Verlag nicht ermittelbar], 2003)
This neighborhood-level study sought to explore the effect of cultural disorganization, in terms of both weakened conventional culture and value heterogeneity, on informal social control, and the extent to which these effects may be conditioned by the level of drug use in the neighborhood. Data for Part 1 were collected from face-to-face and telephone interviews with households in the targeted sample. Part 2 is comprised of data collected from the United States Census 1990 Summary Tape File 3A (STF3A) as well as the United States Census 2000 Population counts, Lexington and Louisville police crime incident reports, and police data on drug arrests. The responses gleaned from the survey used in Part 1 were aggregated to the census block group level, which are included in Part 2.